The implementation of industrial byproduct in malaysian peat improvement: A sustainable soil stabilization approach - Ahmad, A. (MDPI, 2021)
Peat is a well-known problematic soil associated with poor engineering properties. Its replacement with an expensive competent foundation material is practiced for road embankment construction which is costly and causes greenhouse gas emissions. Therefore, this paper investigated the effectiveness of a byproduct from a metal industry (silica fume) to stabilize peat along with ordinary Portland cement (OPC) through a series of experimental tests. After peat-indexed characterization, a number of standard compaction and mechanical tests were performed on the stabilized and parent peat. For this purpose, nine designated mixes were prepared possessing various combinations of silica fume (SF) and 10â20 OPC. Unconfined compressive strength (UCS) and California Bearing Ratio (CBR) tests were carried out after 7, 14, and 28 days of curing to assess strength enhancement and binder effectiveness, and the microstructural evolution induced by the binders was examined with scanning electron microscopy (SEM). The analysis revealed a substantial improvement in mechanical properties with the incorporation of SF and OPC, ultimately meeting the minimum strength requirement for highway construction (i.e., 345 kPa). A peak UCS of 1063.94 kPa was recorded at 20 SF, and an unsoaked CBR value of 42.95 was observed using 15 SF and 15 OPC after 28 days of curing. Furthermore, the increasing percentage of hydraulic binders exhibited brittle, collapsible failure, while the microstructural study revealed the formation of a dense matrix with a refined pore structure in the treated peat. Finally, a significant statistical analysis was carried out by correlating the test parameters. In this way, rather than stockpiling and dumping, an industrial byproduct was implemented in peat stabilization in an eco-friendly manner. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.